URGENSI PERAN ULAMA DALAM RANAH POLITIK - Muhadi Muhadi (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2018)
In social life, the people always related with the other groups. Thus, inevitably every individual human will be in touch with many interests, needs and ideology that exist in society. The human life can not be separated from political affairs. Political struggle is closely related with the interests and powers of the state or government. Constitutional or governmental issues, ideally politics are used to realize the welfare and interests of the people. Scholars who are involved in political vortex provide a positive influence in national politics, including fighting for the establishment of Islamic Shari'ah. On the other hand, their involvement leads to negative excesses.